2005
DOI: 10.1002/pi.1777
|View full text |Cite
|
Sign up to set email alerts
|

Surfactant concentration effects on amorphous PETG–montmorillonite layered silicate (MLS) nanocomposite films

Abstract: Improvements in the dispersion of montmorillonite layered silicates (MLS) have centered on appropriate surfactant treatment of the MLS, to ensure chemical interaction with the polymer material. Here, polyethylene terephthalate glycol (PETG) nanocomposites made with two MLS cation exchanged with dimethyl dihydrogenated tallow quaternary ammonium at two concentrations, 95 (MLS‐95) and 125 meq (100 g)−1 (MLS‐125), were investigated. The host MLS had a cation exchange capacity (CEC) around 92 meq (100 g)−1. The ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
8
0

Year Published

2008
2008
2011
2011

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 18 publications
2
8
0
Order By: Relevance
“…A similar XRD behavior was reported for nanocomposites of polyethylene terephthalate glycol (PETG), using the 15A and 20A nanoclays 28. It was shown that PETG/15A compounds had substantially better reinforcement than PETG/20A compounds 28.…”
Section: Resultssupporting
confidence: 89%
See 2 more Smart Citations
“…A similar XRD behavior was reported for nanocomposites of polyethylene terephthalate glycol (PETG), using the 15A and 20A nanoclays 28. It was shown that PETG/15A compounds had substantially better reinforcement than PETG/20A compounds 28.…”
Section: Resultssupporting
confidence: 89%
“…26,27 A similar XRD behavior was reported for nanocomposites of polyethylene terephthalate glycol (PETG), using the 15A and 20A nanoclays. 28 It was shown that PETG/15A compounds had substantially better reinforcement than PETG/20A compounds. 28 The XRD peaks of 20A compounds shifted to lower angles and 15A showed no change, which was similar to our observations in Figure 4.…”
Section: Morphology Of Fkm/clay Nanocompositesmentioning
confidence: 99%
See 1 more Smart Citation
“…These increases are due exclusively to the OMMT presence, because the orientation, as measured by means of birefringence, was the same in the pure PCTG and in the PNs. A case where the OMMT does not contribute to birefringence, as measured by FTIR, has also been observed in PETG-based [36] PNs. A linear increase in properties such as the modulus is often seen in PNs, [4,55] although at high OMMT content the slope decreases.…”
Section: Nanostructurementioning
confidence: 89%
“…[33] A methyl tallow bis(2-hydroxyethyl) ammonium organic modification led to better dispersion than octadecylamine or dodecylamine modifications. [34] In the case of 1,4-cyclohexanedimethanol-terephthalic acid-ethylene glycol copolymer (PETG), the effects of the organoclay presence on the viscoelastic properties [35] and on the properties of its films [36,37] were studied. However, to our knowledge, no work has been published based on PCTG, which is a copolymer with the same components as those of PETG, but with different proportions of the chemical groups.…”
Section: Introductionmentioning
confidence: 99%